Coronary artery atherosclerosis in reproductive age group women-an autopsy study - Chaithra R Jadhav; Fremingston Marak; Bharathi Pradeep (Asian Journal of Medical Sciences)
Background: Atherosclerosis is the most common coronary artery disease (CAD). It leads to the blocking of arteries and myocardial infarction (MI). Many studies are focused on men. The aim of this study is to look at the prevalence of coronary atherosclerosis, its severity, and arteries involved in postmortem hearts in reproductive age group women.